2013
DOI: 10.1063/1.4804379
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency plasmonic state and negative permittivity spectra of coagulated Cu granular composite materials in the percolation threshold

Abstract: Tunable radio-frequency negative permittivity in nickel-alumina "natural" meta-composites Appl. Phys. Lett.Negative permittivity and permeability spectra of Cu/yttrium iron garnet hybrid granular composite materials in the microwave frequency range Appl. Phys. Lett. 103, 261906 (2013); 10.1063/1.4858976Frequency dependence of effective permittivity of carbon nanotube composites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…(5). A similar phenomenon was also reported in the graphene and carbon nanotube composites, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 where f p was found to closely associated with the conductivity of composites, and moved to higher frequency with increasing the loading of carbon [27,48,49]. Dielectric loss is conventionally described by the ε'' or by tanδ.…”
Section: Conduction and Reactancementioning
confidence: 62%
See 1 more Smart Citation
“…(5). A similar phenomenon was also reported in the graphene and carbon nanotube composites, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 where f p was found to closely associated with the conductivity of composites, and moved to higher frequency with increasing the loading of carbon [27,48,49]. Dielectric loss is conventionally described by the ε'' or by tanδ.…”
Section: Conduction and Reactancementioning
confidence: 62%
“…In 2000, the simultaneously negative permittivity and permeability were achieved in an "artificial" meta-materials composed of periodic metallic wire arrays by Smith et al [7], and the phenomenon of negative refraction was observed in this double negative (DNG) medium [8]. After that, materials with tunable negative electromagnetic parameters have attracted ever-increasing attention [9][10][11][12][13][14][15]. Some "real" random materials consisting of magnetic, dielectric or metallic component have been fabricated to achieve negative permittivity and/or negative permeability in various frequency ranges by adjusting their compositions and microstructures [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…In general, the bulk iron plasma frequency is nearly 9.9 Â 10 5 GHz 30 and collision frequency x s is usually smaller than it by two orders of magnitude. 23 The iron particles embedded in alumina matrix which leads to the dilution of electron concentration and the increase of effective electron mass, so a low frequency plasmonic state, which was also reported in Cu composites, 20,31 was obtained and the f p was dramatically reduced. Amounts of electrons were restricted by alumina particles and boundaries, which suppress the collision between electrons and result in the decrease of x s .…”
mentioning
confidence: 80%
“…[16][17][18] Recently, the investigations show that negative permittivity or negative permeability, which was derived from intrinsic properties, can be also obtained in random composites. [19][20][21][22][23] It is indicated that the negative permittivity is attributed to the plasma oscillation of the conduction electrons 19 and negative permeability can be achieved in some magnetic metal-matrix composites 14,24 or ferrites 25,26 due to magnetic resonance. In the previous investigations, 21,23 we find it is not easy to effectively increase the ferromagnetic iron content and widen the frequency range with DNG characteristic.…”
mentioning
confidence: 99%
“…The novel is that both the negative e (e \ 0) and the negative permeability (l \ 0) are obtained simultaneously, i.e., the double negative properties are realized in cermet [8,9]. After this novel double negative material (DNMs) of cermet was published, the random composites for DNMs attracted much attention in materials community [10][11][12], because the privilege of these exactingly designed periodic composites (metamaterials) was broken to exhibit double negative properties [13,14]. Furthermore, the experimental results and theoretical analysis in our previous work indicate that the content and morphology of the metal play a significant role in adjusting e and l [15].…”
Section: Introductionmentioning
confidence: 97%